Chemical Constituent and Antimalarial Activity based on Inhibition of Heme Polymerization from Water Extract of Yellow Root (Arcangelisia flava L. Merr) - Yatri Hapsari; Partomuan Simanjuntak; Wien Kusharyoto; Sumi Hudiyono (Departemen Kimia, 2019)
In developing countries, malaria remains a disease that can spread easily and caused death. Malaria is an infectious disease caused by Plasmodium sp involving female anopheles masquitos during its transmission. Arcangelisia flava L. Merr has been investigated earlier that it can inhibited P. falciparum growth. Method of antimalarial activity based on inhibition of heme polymerization can confirm one of the mechanism of antimalarial drugs. The aim of this research to study further antimalarial activity and IC50 based on inhibition of heme polymerization and determine the chemical constituent from water extract of A. flava L. Merr. This research was conducted through several steps, namely 1) water extraction, 2) column chromatography (SiO2 ; (i) CH2Cl2-MeOH=10:1 1:1 (ii) n-hexane: EA=1:1; CH2Cl2-MeOH=10:1 1:1), 3) antimalarial assay, 4) identification of chemical constituent using FTIR and GC-MS. Results of this research are water extract of A. flava L. Merr has IC50 601 ppm and identification of chemical constituent using FTIR and GC-MS was assumed as stigmastan.